Supplementation with eicosapentaenoic and docosahexaenoic acids during late gestation alters fatty acid profiles in ewe colostrum, milk, and plasma, and lamb plasma - Carranza Martin, Ana Cristina (2025)
Our aim was to evaluate the effects of increasing dietary levels of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) during the final third of gestation on plasma and milk fatty acid (FA) profiles of ewes and their offspring. Additionally, correlation between maternal and offspring plasma, colostrum, and milk FA profiles were examined. Seventy-two pregnant ewes (92.2 ± 2.94 kg body weight at d 100 of gestation) were blocked by body condition score and randomly assigned to one of three diets containing 0, 1, or 2% of a Ca salt of FA enriched with EPA and DHA during the last 50 d of gestation. Animals were housed in 8 pens per treatment (3 ewes per pen) during the supplementation period. At lambing, all ewes were penned together and offered a diet without FA supplementation. For FA profile, blood samples were collected from ewes at d -20 prepartum, at lambing, and d 15 postpartum. Lamb plasma samples were obtained at birth (0.5 to 8 h post-suckling). Colostrum (0.5 to 8 h postpartum) and milk (d 15 postpartum) were also collected. Data were analyzed using a randomized complete block design. The model included the fixed effects of the treatment for lamb plasma FA profile; and the fixed effects of treatment, time, and their interaction for ewe plasma and colostrum and milk FAprofile. Supplementation with EPA and DHA increased (diet by time interaction; P ≤ 0.06) the polyunsaturated FA (PUFA; C20:40, C20:5, and all omega 3) in ewe plasma until lambing but was similar between treatments 15 d post lambing. Colostrum from supplemented ewes showed greater PUFA (C22:5 and C22:6) concentrations and the difference decreased in the milk (diet by time interaction; P < 0.01), although the colostrum PUFA increase was not correlated with most individual plasma PUFA (C18:2, C20:3n6 and n3, C20:4, C20:5, C22:5, and C22:6), except for C18:3, which showed a positive association (P = 0.03). Furthermore, colostrum PUFA concentrations were positively correlated with the FA composition of lamb plasma post-suckling (P < 0.02). The PUFA concentrations were also increased in lamb plasma at lambing (P < 0.01), suggesting potential effects on neonatal lipid metabolism. These findings demonstrate that dietary supplementation with EPA and DHA, initiated 50 days before lambing and terminated at parturition, can alter the FA composition of maternal plasma, colostrum, and milk, and also influence the plasma FA profile of the offspring.